Pemanfaatan Lahan Pembuangan Sampah menjadi Apotek Hidup di SD Negeri 34 Mataram - Muhammad Abi Rizky; Zikrullah, M. Riki; Johan, M. Syidqi; Rahmatullah, Nikmat; Kawianjana, I Dewa Gede; Zulhijri; Izza Pratama; Al Amin, Naufal Daffa; Maitsalana, Nisrina (Rengganis Jurnal Pengabdian Masyarakat, 2024)
Waste is one of the problems faced by every city, not only in Indonesia but also becoming a global problem. One reason is that the behavior of primary to secondary school students is also involved in contributing large amounts of garbage and decreasing the quality of the environment, especially in the school environment or other educational institutions. Such a clean and healthy lifestyle should also be implemented in the school environment. SD State 34 Mataram is one of the schools that needs to infuse insights about environmental health. One of the efforts that can be done in SD State 34 Mataram is by carrying out activities of cleaning and administration of the school environment as well as as as a living pharmacy land. In the process of implementation of this activity started with the permits on the part of the school, discussion of schedules, gotong royong land cleaning, creation of gapura, land renovation, planting and ended with evaluation activities. The result of this activity is the awareness of students about the importance of healthy living behavior especially in the school environment. With the help of this living pharmacy, students can also gain insights related to medicinal plants and their properties.